Handbook of psychology in legal contexts David Carson and Ray Bull - Carson, David (Wiley, 2003)
This second edition of this handbook highlights the developing relationship between psychology and the law, including material on the provision of psychological assessments to the courts, the interaction between psychologist and other professionals and decision-making by judges and juries.